جدلية القراءات القرآنية والأحرف السبعة - بولخطوط, محمد (جامعة الوادي - University of Eloued, 2019)
عرفت مسألة القراءات القرآنية وعلاقتها بالأحرف السبعة تضاربا شديدا، واختلافا واسعا بين العلماء والباحثين في ميدان الدراسات القرآنية، حيث ذهبوا في ذلك مذاهب شتّى، كلّ مذهب له ركائزه وأسسه المعتمدة في تبيان الحدود القائمة بين القراءات والأحرف. وعلى هذا الأساس نحاول في هذه الورقة البحثية عرض أبرز هذه الآراء والمواقف، محاولين إيجاد مخرج لهذه القضية، التي كثيرا ما أثارت الجدل نظرا لتشابك وتداخل المفاهيم والتصوّرات. The relation between the different modes of recitation or readings (qira'at) and the Seven dialects of the Quran (7 ahruf) has known a huge conflict and diversity among the scholars and researchers in the study of the Holy Quran. This conflict resulted in the appearance of several doctrines each aiming to shed light on the boundaries between the two concepts of qira'at and ahruf. This research paper,in turn, aims to showcase the most prominent views and opinions concerning this subject seeking to reach a solution to the issue.
مقال
Keywords: القراءات القرآنية ; الأحرف السبعة ; القرآن الكريم; modes of recitation (qira'at) ; the seven dialects in the Quran (7 ahruf) ; the ; holy ; qu ; ran